2017
DOI: 10.1097/01.nme.0000525552.06539.02
|View full text |Cite
|
Sign up to set email alerts
|

Strangulation

Abstract: Patients who've been strangled are at risk for negative outcomes, both medical and psychological. Learn how to spot the signs and symptoms, and how best to care for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Strangulation is a painful experience (Turkel, 2010) and may cause immediate symptoms such as loss of consciousness and loss of sphincter control; however, symptoms may appear days and even weeks afterwards, including bruises, brain injury, bleeding, stroke, difficulty swallowing, memory loss, and internal injuries that may result in death (Armstrong & Strack, 2016; Joshi et al, 2012; Scannell, MacDonald, & Foster, 2017; Wilbur et al, 2001). The seriousness of nonfatal strangulation in the context of domestic violence has been further supported by studies that have shown a link between experiencing nonfatal strangulation during a domestically violent relationship and an increased likelihood of intimate partner homicide (Campbell, Glass, Sharps, Laughon, & Bloom, 2007; Glass et al, 2008).…”
Section: Nonfatal Strangulationmentioning
confidence: 99%
“…Strangulation is a painful experience (Turkel, 2010) and may cause immediate symptoms such as loss of consciousness and loss of sphincter control; however, symptoms may appear days and even weeks afterwards, including bruises, brain injury, bleeding, stroke, difficulty swallowing, memory loss, and internal injuries that may result in death (Armstrong & Strack, 2016; Joshi et al, 2012; Scannell, MacDonald, & Foster, 2017; Wilbur et al, 2001). The seriousness of nonfatal strangulation in the context of domestic violence has been further supported by studies that have shown a link between experiencing nonfatal strangulation during a domestically violent relationship and an increased likelihood of intimate partner homicide (Campbell, Glass, Sharps, Laughon, & Bloom, 2007; Glass et al, 2008).…”
Section: Nonfatal Strangulationmentioning
confidence: 99%
“…Strangulation is a form of asphyxia that results in impairment of oxygen flow in the neck because of external pressure (Scannell et al, 2017). It is used as a violent and lethal form of control in intimate partner relationships.…”
Section: Discussionmentioning
confidence: 99%